OvSynch protocol and its modifications in the reproduction management of dairy cattle herds – an update - Nowicki Arkadiusz; Barański Wojciech; Baryczka Agnieszka; Janowski Tomasz (Journal of Veterinary Research, 2017)
Current knowledge about the function of the reproductive tract and appropriate use of hormonal drugs affords control of the oestrus cycle of cows. One of the hormonal protocols is OvSynch, which enables artificial insemination (AI) to be performed at the precise optimum time without control of the ovaries and uterus. Use of such protocols in reproductive management allows oestrus cycles to be synchronised and cows to be effectively inseminated without oestrous detection, which is time-consuming and difficult in farms with numerous cows. Therefore, OvSynch has become the first management tool for AI and is an alternative method to heat detection. Over the 20 years since its first implementation, OvSynch has been modified many times to improve its reproduction outcomes and widen its use. Besides its original use for heat synchronisation, it is also used in many ovarian disorders as a therapeutic method. This review article describes the possibilities which OvSynch provides, its current modifications, various applications, and the advantages and disadvantages of its use in practice.